Morphological characterization of accesions of capsicum spp. from the germoplasm collection of the colombian corporation for agricultural research (corpoica) c.i. palmira (2012)
68 accessions from the Capsicum collection of the Colombian Corporation for Agricultural Research (Corpoica), Palmira were morphologically characterized by using 12 quantitative and 10 qualitative descriptors. For the principal components analysis the variables with highest contribution were asso- ciated to plant architecture and fruit descriptors and their explained 70.8% of total variability. 7lassi- fication analysis based on quantitative data sho9ed ; groups but did not allo9 discrimination bet9een species. For the multiple correspondence analysis 8%. and amp;% of the variability 9as explained by variables related 9ith fo9er and fruit traits. =he classification analyses using qualitative descriptors sho9ed and amp; groups and allowed discrimination of C. baccatum species. The discriminant analysis showed that C. annuum, C. frutescens, and C. chinense are phylogenetically closely related.